The Relationship between Religiosity, Self-Interest, and Impulse Buying: an Islamic Perspective - Arif Hoetoro; Muhammad Said Hannaf (Ekonomi Syariah IAIN Kudus, 2019)
The expansion of e-commerce dramatically changes the spending patterns which are found a significant number of impulse buying. Practical method and easy way to buy specific goods from e-commerce might be an important factor why customers spent their money more impulsively. Researches on this phenomenon showed that psychological values emerged from religiusity condition and self-interest encouragement play as self-regulation for controlling impulsive buying behavior. Viewed from Islamic economic perspective, this study seeks to configurate self-interest (al-nafs) into three levels namely al-nafs al-ammarah, al-nafs al-lawwamah, and al-nafs al-muthmainnah when al-nafs involved in online impulse buying. The first two layers of al-nafs refer to the level of self-interest which are material oriented, whereas the last one represents the highest level of self-interest which is spiritual oriented. By employing 134 repondents from e-commerce customers in Jakarta, the research findings revealed that there was no relationship between religiusity and al-nafs al-ammarah and al-nafs al-lawwamah. However, al-nafs al-ammarah (sig.= 0.000) and al-nafs al-lawwamah (sig.=0.040) positively influenced impulse buying. Meanwhile, there was strong relationship between religiusity and al-nafs al-muthmainnah (sig.= 0.000) in which this highest level of self-interest did not have relationship with impulse buying. These research findings have important implications that in order to regulate impulsive buying behavior, customers should control their self-interest and make it to be al-nafs al-muthmainnah.